KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU DI SD NITIKAN MUHAMMADIYAH YOGYAKARTA - Yusutria; Abdul Hopid; Rina Febriana; Nisa Amalia Kholifah; Santi Mahmuda; Dzaky Fauzan Abid (LP2M Institut Agama Islam (IAI) Muhammadiyah Sinjai, 2022)
The principal's leadership is very effective in increasing teachers' work motivation in carrying out their responsibilities and impacting the quality of education. The study aimed to determine the principal's leadership in improving teacher professionalism and the supporting and inhibiting factors at SD Nitikan Muhammadiyah Yogyakarta. This research is descriptive qualitative, data collection through interviews with purposive sampling technique, observation, and documentation. Sand sources of data from school principals and teachers amounted to 25 people. The results of the research on the principal's strategy to improve the quality and professionalism of teachers are to motivate, encourage and organize seminars/training related to knowledge and understanding of the development of information technology, reward, and punishment for teachers. In addition, school principals strive to meet content standards, process standards, graduation capacity standards, facilities and infrastructure standards, management standards, funding standards, teacher and staff standards, and teacher education standards and standards. While the supporting factors are providing equal opportunities for teachers to develop their pedagogical and professional capacities by participating in various teaching and training activities, based on knowledge and adapted to needs and budget allocations. The inhibiting factor is the lack of internal motivation due to busy teaching time for priority reasons.